Comparison of CT number between conventional CT and ImaSim software - Baharudin, Muhammad Firdaus (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2015)
This study determines the suitability of ImaSim CT simulation software, as CT Image generation and analysis. CT images of various tissues are obtained by using conventional CT and the CT simulation software. The value of CT number of various tissues which represents the tissue's density is compared between conventional CT method and ImaSim software. To obtain the CT image conventionally, CIRS 062 Electron Density CT Phantom was used and 5 plug phantoms were used which are air, lung exhale, adipose, water and dense bone (1000 mglcc HA). The same types of tissues were used to simulate in the CT simulation software ImaSim and all the CT numbers were recorded. Both conventional and simulation method uses fixed tube current-time product at 260 mAs at three different energy which are 80 kVp, 120 kVp and 140 kVp. The value of CT number obtained for conventional CT and ImaSim software is in the acceptable range of CT numbers of each specific tissues. The chi-square calculated gives low value for air, fat and water which is less than 2.98. Chi-square value for lung and bone gives high value which is up to 200. Therefore the accuracy of CT number obtained from ImaSim software specifically for lung and bone is questionable as the value is deviated from the standard value and the CT number obtained conventionally.